Factors Related to Acute Respiratory Tract Infections in Patients (Comparative Study at Morosi Health Center) - Febriana Hende, Hendry; Supodo, Timbul; Azizi Jayadipraja, Erwin (Waluya The International Science of Health Journal, 2023)
Introduction: The impact of industrial areas, namely pollution and environmental damage, is also quite felt by the community, especially around activities not including dust, noise, and pollution due to chemical substances. Method: This type of research is quantitative using a comparative approach. The population in this study amounted to 1,370 and sample of 301 respondents. Sampling method using Cluster Random Sampling. Result: It is known that the average increase for the attitude variable is 11.83851 with a t-count value greater than t-table (7,315 > 1.61831) and the Action variable with an average increase of 26,27329 and it is known that the t-count for the action variable is greater than t-table (15,611> 1.68299). Conclusion: It was concluded that there was a relationship between environment and Clean and Healthy Life Behavior towards the incidence of ARI and there was a difference in the incidence of ARI between high risk areas (Morosi Village and Porara Village) and low risk areas (Mendikonu Village and Wonua Morini Village).